Pengaruh Inovasi dan Media Sosial terhadap Kinerja UMKM Makanan Halal di Kota Bekasi Utara - Komariah, Neng Siti; Nursal, M Fadhli; Rianto, Muhammad Richo (Jurnal Ilmiah Ekonomi Islam, 2022)
This study examines the relationship between innovation and social media in influencing the performance of halal food SMEs in North Bekasi City. This study uses a quantitative approach that is examined on halal food entrepreneurs in the city of North Bekasi. This study uses the SmartPls data analysis tool with a minimum sample of 100 halal food SMEs in the city of North Bekasi, but in practice from the questionnaires distributed as many as 145 questionnaires were received and only 115 questionnaires could be used in the study. The results of this study found that innovation had no effect on performance while social media had an effect on the performance of halal food SMEs in North Bekasi. This research focuses on the role of innovation and social media in influencing performance. The focus of research on halal food MSMEs is expected to be a new sector that is studied in many types of MSMEs. The city of North Bekasi with a large number of MSMEs and a scattered Muslim population makes the results of this study more useful for the wider community.